Magnetic fibre and paper for information storage - Ong B.H.; Zakaria S.; Ahmad S.; Abdullah M.; Yusoff M.N.M.; Liang M.S.; Van De Ven T.G.M. (2023)
Magnetic paper via lumen loading process was prepared from neverdried and dried kraft pulp. Polyethylenimine (PEI) was used as retention aid during the inter-stage treatment. The paper produced from the magnetic pulp showed an increase of magnetic properties as the loading increased. The physical properties of the paper such as tensile index, burst index, tear and folding endurance showed a reduction in the strength value as the loading capacity increased. The lumen-loaded paper shows better physical properties than conventionally loaded paper. The flocculation study shows that the magnetic colloid exists in multi particles aggregates form in water solution, which caused by magnetodipole interaction.